The living conditions of the princesses in the palaces of foreign countries A reading of the political marriages of the Mitanni and Kashi with the kingdoms of the ancient Near East - marf, Asst.Prof.Dr.dlshad aziz marf (Sulaimani Journal for Humanities, 2026)
Intermarriage between neighboring and distant kingdoms and ruling families in the ancient Near East was very popular in the fourteenth century BC and the following centuries. Cuneiform texts, especially dowry texts and royal letters sent by the kings (fathers or brothers of the princesses) about the preparations of their weddings to inquire about the condition of their daughter/sister princesses in the foreign palaces of their neighboring kingdoms, are very detailed and reveal hidden aspects of their circumstances in the joys and sorrows of their lives. This paper focuses on hidden aspects of the living conditions of the Kassite and Mitanni princesses who married kings or princes of ancient Near Eastern kingdoms in the political marriages and vice versa. By interpreting the evidence of cuneiform texts (dowry and royal correspondences), the artistic and the archaeological evidence, also presents a wider picture of the hidden side of the lives of these princesses away from home in the foreign palaces, with some untold details revealed in this evidence.